Environmental Enrichment as a Strategy to Confront Social Isolation Under the COVID-19 Pandemic - Davim, André; Trindade da silva, Laíse; Vieira, Paulo (Frontiers in Behavioral Neuroscience, 2021)
The moment of social isolation experienced by the world population due to the pandemic of COVID-19 tends to trigger behavioral changes of different orders and on an exponential scale, regardless of social class, age, gender or ethnicity. Environmental enrichment presents itself as an important strategy to face the social isolation imposed by the pandemic, in order to act as an important agent of induction of biological factors for cognitive and emotional development, favoring a better possibility of adaptation to isolation.